Validation of the French version of the alcohol, smoking and substance involvement screening test (ASSIST) in the elderly - Khan Riaz; Chatton Anne; Thorens Gabriel; Achab Sophia; Nallet Audrey; Broers Barbara; Calzada Gerard; Poznyak Vladimir; Zullino Daniele; Khazaal Yasser (BMC, 2012)
Abstract Background Substance use disorders seem to be an under considered health problem amongst the elderly. The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), was developed by the World Health Organization to detect substance use disorders. The present study evaluates the psychometric properties of the French version of ASSIST in a sample of elderly people attending geriatric outpatient facilities (primary care or psychiatric facilities). Methods One hundred persons older than 65 years were recruited from clients attending a geriatric policlinic day care centre and from geriatric psychiatric facilities. Measures included ASSIST, Addiction Severity Index (ASI), Mini-International Neuropsychiatric Interview (MINI-Plus), Alcohol Use Disorders Identification Test (AUDIT), Revised Fagerstrom Tolerance Questionnaire-Smoking (RTQ) and MiniMental State(MMS). Results Concurrent validity was established with significant correlations between ASSIST scores, scores from ASI, AUDIT, RTQ, and significantly higher ASSIST scores for patients with a MINI-Plus diagnosis of abuse or dependence. The ASSIST questionnaire was found to have high internal consistency for the total substance involvement along with specific substance involvement as assessed by Cronbach's α, ranging from 0.66, to 0.89 . Conclusions The findings demonstrate that ASSIST is a valid screening test for identifying substance use disorders in elderly.